A lightweight rotationally arranged auxetic structure with excellent energy absorption performance. (March 2022) - Zhang, Wei-Ming; Li, Zhen-Yu; Yang, Jin-Shui; Ma, Li; Lin, Zhuang; Schmidt, Rüdiger; Schröder, Kai-Uwe
Abstract: As one of the representatives of advanced lightweight cellular materials, the auxetic structure has a great potential for energy absorption due to its unique deformation mechanism, which makes a very promising application prospect in the fields of aerospace, vehicle and engineering protection. In order to further increase the energy absorption capacity of auxetic structures, this paper designed and characterized a novel two-dimensional (2D) lightweight rotationally arranged auxetic structure. The elastic properties, plastic collapse stress and specific energy absorption (SEA) of the novel auxetic structure were systematically investigated through theoretical calculations, numerical simulations and experimental method. Our results verify that the proposed theoretical model is accurate and applicable. The rotationally arranged shape and stable triangular design inside unit cells lead to an excellent energy absorption capacity, which is significantly higher than that of conventional auxetic structures (star-shaped honeycombs and re-entrant hexagonal honeycombs). Moreover, the SEA of novel structure has extremum conditions, by which the optimal relative density can be determined. According to different user requirements, the novel structure can be designed as the best energy absorption type or the most concise and lightweight type by adjusting geometrical parameters. Graphical abstract: Image 1 Highlights: The present rotationally arranged auxetic structures show high energy absorption. Extremum conditions of specific energy absorption are investigated. Mechanical properties can be designed by adjusting geometric parameters.